Kajian Pengelolaan Personnel Files Berbasis Elektronik: Studi Kasus Kantor Regional II Badan Kepegawaian Nasional (BKN) Surabaya - Failina Zuhrotun Napsi (Program Studi Kearsipan, DBSMB SV UGM, 2019)
This paper examines the procedures for managing electronic files based personnel. The research locus is in Regional Office II of the National Personnel Agency (BKN) Surabaya. Human resource management organizations create personnel files or personnel files that are managed in a certain way in accordance with the vision and mission. Basically, personnel files created by the State Personnel Agency are a vital type of archive. The data used consists of primary data and secondary data. Data collection methods used in this study are observation, interviews, and literature study. Observations or observations made at the Regional Office II of the National Personnel Agency (BKN) Surabaya. The interview aims to add information through the staffing administration. Literature study is used to collect data in order to strengthen the exposure that has been described by the author. Management of personnel files at Regional Office II of the Surabaya National Personnel Agency (BKN) based on the storage media is done physically and electronically. Electronically, the management of personnel files is carried out starting from scanning or scanning, storing and maintaining.